Methods of Memorizing Mutashabihat Verses: Study on Darul Quran, JAKIM and Department of al-Quran and al-Qiraat KUIS - Abd Muhaimin Ahmad; Muhammad Hafiz Saleh; Muhammad Arif Musa; Norazman Alias; Khairul Anuar Muhammad (Universiti Sultan Zainal Abidin, 2024)
Volume: 22 No: 3 (page: 77-85)